Isolation and Testing of Bacteria from Steroid Compounds obtained from Anting-anting Leaf (Acalypha indica L.) - Ditya Vega Fauzia; Dewi Kusrini; Enny Fachriyah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Isolation of steroid compounds from the leaves of the earrings (Acalypha indica L.) and the antibacterial test has been performed. This study aims to obtain information about secondary metabolite compound leaves of Anting-anting, obtaining and identifying steroid isolates from the leaves of Anting-anting and knowing the antibacterial activity of the positive fraction of steroid compounds. The research stages include sample preparation, phytochemical test, isolation, separation, purification of steroid compounds, identification of steroid isolates using LC-MS/MS, and antibacterial test by paper disc method. The results of phytochemical screening show that the leaves of the earrings contain alkaloid compounds, flavonoids, steroids, saponins, tannins, and quinones. From the results of steroid isolation, we found steroid isolates weighing 0.0065 grams (0.0058%). Identification of steroid isolates using LC-MS/MS at a retention time of 7.49 min with [M+H]+ 399 m/z indicated the presence of a brassicasterol compound. The results of antibacterial test of fraction A from chloroform extract containing steroid compound showed antibacterial activity against Staphylococcus aureus bacteria and Escherichia coli bacteria.